2006
DOI: 10.1103/physrevb.74.165117
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of charge-orderedFe3O4from calculated optical, magneto-optical Kerr effect, and OK-edge x-ray absorption spectra

Abstract: The electronic structure of the low-temperature (LT) monoclinic magnetite, Fe 3 O 4 , is investigated using the local spin density approximation (LSDA) and the LSDA+U method. The selfconsistent charge ordered LSDA+U solution has a pronounced [001] charge density wave character.In addition, a minor [00 1 2 ] modulation in the phase of the charge order (CO) also occurs. While the existence of CO is evidenced by the large difference between the occupancies of the minority spin t 2g states of "2+" and "3+" Fe B ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 75 publications
3
46
0
Order By: Relevance
“…Furthermore, it is clear that our results are consistent with the values obtained using XMCD by Goering et al, 17 and with recent theoretical predictions. 6,7 In conclusion, our experiments have found that there is a spin moment of approximately 4 B for all temperatures and for the three principal crystallographic directions. Consequentially, the orbital moment, determined by comparison with bulk magnetometry, is therefore nearly fully quenched, in agreement with Goering et al 17,19 We do not observe the significant orbital moments reported by Huang et al 15 or Li et al 20 No evidence of any anomalies in the spin or orbital moments at the Verwey transition is observed.…”
Section: ͑1͒supporting
confidence: 54%
See 2 more Smart Citations
“…Furthermore, it is clear that our results are consistent with the values obtained using XMCD by Goering et al, 17 and with recent theoretical predictions. 6,7 In conclusion, our experiments have found that there is a spin moment of approximately 4 B for all temperatures and for the three principal crystallographic directions. Consequentially, the orbital moment, determined by comparison with bulk magnetometry, is therefore nearly fully quenched, in agreement with Goering et al 17,19 We do not observe the significant orbital moments reported by Huang et al 15 or Li et al 20 No evidence of any anomalies in the spin or orbital moments at the Verwey transition is observed.…”
Section: ͑1͒supporting
confidence: 54%
“…1,2 This is accompanied by a transition to a low symmetry structure, the precise nature of which is still being discussed. [3][4][5] Above this transition, band-structure calculations predict that Fe 3 O 4 should be a half metal, with conduction only associated with the minority spin electrons 6,7 and thus possess 100% spin polarization. Experimentally somewhat lower values have been reported ͓for example, 40% ͑Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic state in the low-temperature phase has been investigated using LDA+U calculations [16][17][18][19] based on the monoclinic lattice structure shown by Wright et al 4) From the LDA+U calculations, a state with simultaneous charge and antiferro-orbital ordering is obtained. In the state, the B2a, B2b, and B3 sites are vacant, and the xy orbitals are occupied at the B4 sites.…”
Section: Lattice Distortion and Related Propertiesmentioning
confidence: 99%
“…15) Based on the three-band model, Seo et al have proposed a mechanism of the Verwey transition with a bond dimerisation caused by the Peierls instability, where charge ordering is irrelevant to the transition. 15) Recently, the electronic state in the lowtemperature phase has been investigated using local density approximation+Hubbard U (LDA+U) calculations [16][17][18][19] based on the monoclinic lattice structure shown by Wright et al 4) In the LDA+U calculations, a state with simultaneous charge and antiferro-orbital ordering is obtained.…”
Section: Introductionmentioning
confidence: 99%